Design of Contextual-Collaborative Assure-Based Learning Program Development in Improving Reading Skills and Bilingual Communication Skills of Early Childhood Children - Attaufiqi, Agil Fahmi; Maskud; Maulana, Asep; Fatikh, M. Alfin; Firmansyah, Choiron (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This article aims to describe the design for developing and evaluating the media for learning with a collaborative-contextual model in improving the reading skills and bilingual abilities of early childhood in the Sukorambi Islamic Kindergarten (TK), Jember Regency. This research uses a qualitative type with a descriptive exploratory approach—data collection techniques using in-depth interviews, participatory observation, and documentation studies. The data were then analyzed using the stages of domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis with the validity of the data, the credibility of the triangulation method and sources, and confirmability. Based on the research findings, it was concluded that the six stages in the design of contextual-collaborative assured-based learning program development in improving reading skills and bilingual communication skills are as follows: Analysis of Early-Age Learners as Digital Natives: Determining learning objectives, selecting methods, media, and materials (including the application of student-centered methods, developing an Outline of Content for Podcast Media, creating Podcast Media Scripts, and formulating Bilingual Learning Implementation Plans). Utilizing media and teaching materials involves reviewing and preparing materials, establishing conducive learning environments, engaging learners, and ensuring enriching learning experiences. Additionally, active learner involvement and thorough evaluation are essential components.